Estimation of retention parameters from temperature programmed gas chromatography - Leppert, Jan; Brehmer, Tillman; Wüst, Matthias; Boeker, Peter (Journal of Chromatography A, 2023)
•Fast method for the estimation of retention parameters from temperature programmed GC.•Initial value for retention parameters based on elution temperatures.•Estimated retention parameters can be used to predict retention times. A fast and reliable method is presented to evaluate retention parameters of the distribution-centric 3-parameter model from temperature programed gas chromatographic measurements. Based on a fully differentiable model of the migration of solutes in a gas chromatographic (GC) system, Newton's method with a trust region is used to determine the three parameters, respectively the three parameters and the column diameter, of several solutes as the minima of the difference between measured and calculated retention times. The determined retention parameters can then be used in method development, using the simulation of GC separation. The results of the retention parameters are compared to the parameters determined using isothermal GC measurements and show good agreement, with deviations of less than 0.5% (1.8 K) for the most important parameter of characteristic temperature Tchar. Using the estimated retention parameters, additional GC separations are simulated and compared with measurements. Retention times in additional temperature programmed measurements could be predicted with less than 0.7% deviation. Four to five different temperature programs are enough to determine reliable retention parameters. Unless the column diameter and the column length are exactly known, it is preferable to also estimate the diameter (more precisely the L/d-ratio) together with the retention parameters.